2007
DOI: 10.1088/0960-1317/17/8/015
|View full text |Cite
|
Sign up to set email alerts
|

PCR biocompatibility of lab-on-a-chip and MEMS materials

Abstract: DNA amplification using the polymerase chain reaction (PCR) is an important tool in biotechnology, pathogen surveillance in food, medical and forensic science etc. The PCR technique is now an important part of the research in and development of miniaturized biochemical analysis systems. However, reduced or no DNA amplification at all is an important challenge for microfabricated PCR devices due to a negative interaction between PCR chemicals and the surrounding environment, i.e. the materials encapsulating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 37 publications
0
53
0
Order By: Relevance
“…SU-8 was found to be inhibitory both with and without BSA (RBI < 8.2 × 10 1 ) in the PCR mixture. Untreated SU-8 had already been shown to be inhibitory [11,44].…”
Section: Materials Inhibitory Effectmentioning
confidence: 99%
“…SU-8 was found to be inhibitory both with and without BSA (RBI < 8.2 × 10 1 ) in the PCR mixture. Untreated SU-8 had already been shown to be inhibitory [11,44].…”
Section: Materials Inhibitory Effectmentioning
confidence: 99%
“…We suggest that further research be performed on the biocompatibility of DuPont's 951 LTCC from various lots. Other materials, such as silicon, which are being used for the construction of PCR devices, also show partial inhibition of PCR reactions through the adsorption of the enzyme Taq polymerase [19][20][21][22].…”
Section: Ltcc Inhibition Of Pcrmentioning
confidence: 99%
“…This result suggested that some interaction between the LTCC and Taq polymerase occurred to reduce enzyme activity. At lower concentrations much of the polymerase may be adsorbed to the surface of the LTCC, which has been shown to be the cause of inhibition in reactions in the presence of silicon [19][20][21][22]. However, when the concentration of polymerase is increased, more of the enzyme remains in solution, resulting in the concomitant increase in PCR product.…”
Section: 21taq Polymerase Is Limiting In the Presence Of Ltccmentioning
confidence: 99%
See 2 more Smart Citations